Correction to: Three-dimensional morphometric analysisreveals time-dependent structural changesin microglia and astrocytes in the centralamygdala and hypothalamicparaventricular nucleus of heart failure rats - Ferdinand Althammer; Hildebrando Candido Ferreira-Neto; Myurajan Rubaharan; Ranjan K. Roy; Atit A. Patel; Anne Murphy; Daniel N. Cox; Javier E. Stern (Journal of Neuroinflammation, 2020)
An amendment to this paper has been published and can be accessed via the original article.